ANALYSIS OF MUSIC TEACHING METHODS IN KARAWITAN MUSIC LEARNING ACTIVITIES - Posumah, Christabela Gabriela; Takalumang, Lucyylle; Sunarmi, Sri (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to identify and describe the learning of music art in students of SMA Negeri 1 Tondano. The researcher obtained this degree through the Field Experience Program (PPL) at SMA Negeri 1 Tondano, as well as taking Music Art courses at UNIMA. Relevant theories such as the definition of learning, learning that involves students, teachers, curriculum, learning materials, and learning methods are used in this research as a foundation for achieving research objectives. The research method used is descriptive qualitative with data collection techniques through observation. The results showed that music learning at SMA Negeri 1 Tondano uses various methods, including lecturing, demonstration, and practice. Although most students are interested and enjoy the learning methods used, there are also students who feel bored due to the lack of variety. Therefore, this study recommends that teachers adopt different learning strategies, develop media, and maintain students’ interest so that music learning can take place effectively and enjoyably. It is hoped that the results of this study can help in improving the quality of music learning at SMA Negeri 1 Tondano.